Magnesia, method for manufacturing the same, highly thermally conductive magnesia composition, and magnesia ceramic using the same

By forming a surface oxide layer on MGO granules through donor addition and heat treatment, the method addresses moisture absorption and high sintering issues, resulting in improved thermal conductivity and low-cost ceramic fillers for TIMs.

JP2025016583APending Publication Date: 2025-02-04KOREA INST OF MATERIALS SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024188426
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-13
Filing Date
2024-10-25
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

Existing ceramic fillers for thermal interface materials (TIM) face issues with moisture absorption, leading to reduced thermal conductivity and separation from polymer materials, and high sintering temperatures hinder the use of magnesia (MGO) as a high-thermal conductivity filler.

Method used

A method involving the addition of donors and organic solvents to MGO powder, followed by drying and heat treatment, forms a surface oxide layer on MGO granules with different compositions, improving moisture resistance and allowing low-temperature sintering below 1500°C.

Benefits of technology

The method enhances moisture resistance and thermal conductivity of MGO, enabling its use as a low-cost, high-thermal conductivity ceramic filler for TIMs, with improved sintering characteristics and reduced moisture absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016583000001_ABST
    Figure 2025016583000001_ABST
Patent Text Reader

Abstract

To provide magnesia excellent in moisture resistance and capable of being applied to a ceramic filler for a thermal interface material, and to provide a method for manufacturing the same.SOLUTION: This invention discloses: magnesia that can be produced from a powder to form granules of various shapes and sizes, and which, after heat treatment with addition of a donor, forms a surface oxide layer having moisture resistance, thereby improving low moisture resistance of MgO; and a method for producing the same. The present invention also discloses a highly thermally conductive magnesia composition in which a donor is added to MgO to lower the sintering temperature and improve the thermal diffusivity, and magnesia ceramics using the same. The method for producing the magnesia according to the present invention includes the steps of: (a) forming a mixture by adding the donor and an organic solvent to MgO powder; (b) forming MgO granules with the added donor from the mixture; and (c) heat-treating the MgO granules with the added donor.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnesia for ceramic filler that is used as a thermal interface material by forming a surface oxide layer containing MgO-donor different from that inside the granule on the surface of the MgO granule during heat treatment after adding a donor to MgO powder, and improving moisture absorption resistance, and a method for producing the same.The present invention also relates to a highly thermally conductive magnesia composition that lowers the sintering temperature and improves the thermal diffusion coefficient by adding a donor to MgO, and a magnesia ceramic using the same. [Background technology]

[0002] In manufacturing components such as high-output LEDs and power devices that consume high power and generate a lot of heat, heat dissipation packages are used to ensure the reliability and long life of the components.

[0003] Typically, a heat dissipation package is made up of a highly thermally conductive insulating substrate, a metal heat sink, A thermal interface material (TIM), which is a heat dissipation adhesive, is used between the highly thermally conductive insulating substrate and the metal heat sink.

[0004] Thermal interface materials can act as adhesives to bond highly thermally conductive insulating substrates and metal heat sinks together, or can be used alone as heat dissipation components. These thermal interface materials consist of a composite of a polymer and a highly thermally conductive metal or ceramic filler material.

[0005] Thermal interface materials are primarily used in polymers containing Al2O3 fillers.

[0006] However, the thermal conductivity of the Al2O3 filler material is rather low at 20-30 W / mK, which needs to be improved.

[0007] On the other hand, MgO has a raw material cost equivalent to that of Al2O3, and has a thermal conductivity of 30-60W / mK, which is superior to Al2O3 filler materials. 14 It has a resistivity of more than Ohm·cm and excellent electrical insulation properties. Therefore, when MgO filler is used instead of Al2O3 filler, it can improve the thermal conductivity of Al2O3-based thermal interface materials, making it useful as a filler for TIM.

[0008] However, MgO has a relatively high hygroscopicity, and its thermal conductivity decreases when it absorbs moisture. Furthermore, Mg(OH)2, which is generated on the surface of MgO due to moisture absorption, not only makes it difficult to combine with polymers and makes it difficult to manufacture as a TIM, but also tends to cause problems such as a high possibility of separation from the polymer material due to volume expansion. These points are obstacles to the practical use of MgO as a thermally conductive ceramic filler. For this reason, in order to develop MgO as a thermally conductive ceramic filler for TIM, it is necessary to first develop technology that can improve its resistance to moisture absorption.

[0009] On the other hand, MgO has the advantage of having a high thermal conductivity of 30-60 W / mK compared to alumina (Al2O3).

[0010] However, while alumina (Al2O3) is sintered at approximately 1500~1600℃, magnesia (MgO) has the disadvantage of being sintered at high temperatures of over 1700℃, so the sintering conditions for magnesia (MgO) need to be improved. Although there have been attempts to sinter magnesia (MgO) at low temperatures, there has been no research into heat-dissipating ceramic materials that can be sintered at lower temperatures while maintaining thermal conductivity.

[0011] Therefore, there is a need for research and development of a new, cost-competitive, low-cost, highly thermally conductive oxide material that can be sintered at temperatures lower than 1500°C, the sintering temperature of alumina (Al2O3), while retaining the high thermal conductivity properties of magnesia (MgO). [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Korean Patent Publication No. 10-2016-0014590 (Published on February 11, 2016) Summary of the Invention [Problem to be solved by the invention]

[0013] An object of the present invention is to provide magnesia which has excellent moisture absorption resistance and can be applied to a ceramic filler for a thermal interface material, and a method for producing the same.

[0014] Another object of the present invention is to provide a magnesia (MgO) composition and a magnesia (MgO) ceramic which can ensure both low-temperature sintering (<1500° C.) and high thermal conductivity.

[0015] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and can be more clearly understood from the embodiments of the present invention. Also, it is easy to understand that the object and advantages of the present invention can be realized by the means and combinations thereof described in the claims. [Means for solving the problem]

[0016] The present invention provides a method for producing magnesia (MgO), comprising the steps of: (a) forming a mixture by adding a donor to MgO powder and an organic solvent; (b) drying the mixture; (c) forming donor-doped MgO granules from the dried mixture; and (d) heat-treating the donor-doped MgO granules, wherein the donor-doped MgO granules are heat-treated to form a surface oxide layer on the surface of the MgO granules, the composition of which is different from that of the interior of the MgO granules.

[0017] The present invention also provides a method for producing magnesia (MgO), comprising the steps of: (a) adding a donor and distilled water to Mg(OH)2 powder to form a mixture; (b) drying the mixture; (c) forming donor-doped Mg(OH)2 granules from the dried mixture; and (d) heat-treating the donor-doped Mg(OH)2 granules, wherein the donor-doped Mg(OH)2 granules are heat-treated to form a surface oxide layer on the surface of the MgO granules, the composition of which is different from that of the interior of the MgO granules.

[0018] The present invention also provides magnesia (MgO), comprising: MgO granules; and a surface oxide layer formed on the surface of the MgO granules; wherein the composition of the surface oxide layer is different from the composition inside the MgO granules.

[0019] The present invention also provides a magnesia (MgO) composition that contains TiO2, Nb2O5, ZrO2 or Al2O3 in an MgO matrix and satisfies the following Formula 1, Formula 2, Formula 3 or Formula 4.

[0020] Formula 1 MgO + xwt.% TiO2, Formula 2 MgO+ywt.%Nb2O5 Formula 3 MgO+zwt.%ZrO2 Formula 4 MgO+wwt.%Al2O3 (x, y, z, and w in the above formulas 1 to 4 are 0 <x、y、z、w≦10.0である。) Effect of the Invention

[0021] The method for producing magnesia according to the present invention has the effect of improving the low moisture absorption resistance of MgO by forming a surface oxide layer containing "MgO and donor material" on the surface of MgO granules during heat treatment, which is different from the inside of the granules. Such magnesia can be used as a ceramic filler for thermal interface materials.

[0022] In addition, the present invention adds a ceramic composition containing one or more of TiO2, Nb2O5, ZrO2, Ga2O3, Mn2O3, B2O3, Fe2O3, SnO2, MnO2, SiO2, V2O5, Ta2O5, Sb2O5, Y2O3, Eu2O3, Er2O3, and Al2O3 to magnesia (MgO), making it possible to sinter magnesia (MgO), which has high thermal conductivity, at a temperature lower than 1500°C while improving the thermal diffusion coefficient of the magnesia (MgO) material, which can be used as a low-cost heat-dissipating ceramic material.

[0023] In addition to the above-mentioned effects, specific effects of the present invention will be described below together with specific matters for carrying out the invention. [Brief description of the drawings]

[0024] [Figure 1] 1 is a conceptual diagram showing the formation of a surface oxide layer by heat treatment during the production of MgO granules of the present invention, and photographs of the surface and internal microstructures. [Diagram 2] Photographs of the microstructure showing the shape and size of MgO granules produced according to the production method of the present invention, and photographs of the surface microstructure before and after heat treatment (1400°C, 2h). [Diagram 3] A photograph showing the difference in resistance to water reaction between MgO raw powder and MgO granules that have been heat-treated (1400°C, 2h) after adding a donor to the MgO powder. [Figure 4] Photographs of the fracture surface microstructures of a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen (left) and a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5 specimen (right) that were heat treated at 1400℃ for 2 hours, showing the thickness of the surface oxide layer. [Diagram 5] Energy Dispersive X-Ray Spectroscopy (EDS) analysis results and microstructure photographs confirming the formation of a surface oxide layer containing MgO-donors in a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen heat-treated at 1400℃ for 2 hours. [Figure 6]1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a TiO2 composition to magnesia (MgO) and sintering the same. [Figure 7] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a Nb2O5 composition to magnesia (MgO) and sintering the same. [Figure 8] 1 is a graph showing the change in thermal diffusivity and the change in density of a test piece obtained by adding a small amount of TiO2 (or Nb2O5) composition to magnesia (MgO) and sintering it. [Figure 9] 1 is a graph showing the change in thermal diffusivity and the change in density of a specimen obtained by adding 0.3 wt. % TiO2 + a trace amount of Nb2O5 composition to magnesia (MgO) and sintering it. [Figure 10] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a ZrO2 composition to magnesia (MgO) and sintering the same. [Figure 11] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding a 0.3 wt. % TiO2 + 0.3 wt. % Nb2O5 + ZrO2 composition to magnesia (MgO) and sintering the same. [Figure 12] 1 is a graph showing the change in thermal diffusivity of a specimen obtained by adding an Al2O3 composition to magnesia (MgO) and sintering the same. [Figure 13] 1 is a graph showing the change in thermal diffusivity and the change in density of a test piece obtained by adding a composition of 0.3 wt. % TiO2 + 0.3 wt. % Nb2O5 + a trace amount of Al2O3 to magnesia (MgO) and sintering it. [Figure 14] A specimen in which 2.0 wt.% TiO2 composition was added to magnesia (MgO), and a specimen in which 2.0 wt.% ZrO2 composition was added to magnesia (MgO) were sintered at 1400℃ for 2 hours, and then the fracture surface was observed with an electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The above-mentioned objects, features and advantages will be described in detail below with reference to the accompanying drawings, so that those skilled in the art to which the present invention pertains can easily implement the technical idea of ​​the present invention. In the description of the present invention, if a detailed description of a known technology according to the present invention is deemed to make the gist of the present invention unclear, the detailed description will be omitted. Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings are used to indicate the same or similar components.

[0026] Hereinafter, magnesia and its manufacturing method according to several embodiments of the present invention, a highly thermally conductive magnesia composition, and a magnesia ceramic using the same will be described.

[0027] The method for producing magnesia of the present invention includes the steps of adding a donor and an organic solvent to MgO powder to form a mixture, drying the mixture, forming donor-doped MgO granules from the dried mixture, and heat treating the donor-doped MgO granules.

[0028] The donor-added MgO granules are then heat-treated to form a surface oxide layer on the surface of the MgO granules, the surface oxide layer having a composition different from that of the interior of the MgO granules.

[0029] The donor in the present invention means a metal oxide having a higher metal valence than MgO, that is, an oxide having a valence of three or more.

[0030] On the other hand, in the method for producing magnesia of the present invention, Mg(OH)2 is used instead of the MgO powder. When Mg(OH)2 is used, the shrinkage rate (linear) of the sintered body and granules after heat treatment is The shrinkage is shown to be 20 to 40%. This shrinkage rate is significantly different from the 10 to 30% shrinkage rate when MgO is used.

[0031] When producing magnesia using Mg(OH)2 powder instead of MgO powder as the starting material, it is preferable to add distilled water instead of the organic solvent. Magnesia can be produced under the same conditions as in the method for producing magnesia using MgO powder described below, except that the starting materials Mg(OH)2 and distilled water are used.

[0032] The manufacturing method below will be described as a method for producing magnesia using MgO powder.

[0033] In the step of adding the donor and the organic solvent to the MgO powder to form a mixture, the mixture may be formed by mixing the MgO powder with a solution prepared by dissolving and dispersing the donor in the organic solvent.

[0034] A small amount of 0.01 to 10.0 wt.% of a donor containing one or more of TiO2, Nb2O5, ZrO2, Ga2O3, Mn2O3, B2O3, Fe2O3, SnO2, MnO2, SiO2, V2O5, Ta2O5, Sb2O5, Y2O3, Eu2O3, Er2O3 and Al2O3 is added to a total of 100 wt.% of the MgO powder and donor.

[0035] If the amount of the donor added is outside this range, it may be difficult for the magnesia to maintain its moisture absorption resistance and thermal conductivity properties as a ceramic filler for a thermal interface material.

[0036] The donor and organic solvent are added to the MgO powder, and then mixed and crushed by ball milling to form a mixture.

[0037] In the step of forming the mixture, milling may be carried out for 0.5 to 72 hours.

[0038] If the grinding time is too short, less than 0.5 hours, the mixing and grinding effect of MgO and the donor additive may be insufficient, whereas if it exceeds 72 hours, the grinding time is too long and the process may be inefficient.

[0039] The organic solvent may be 2-propanol, absolute alcohol, or distilled water. When distilled water is used, a shrinkage rate of 20 to 40% is observed due to the formation of Mg(OH)2. This shrinkage rate is significantly different from the shrinkage rate of 10 to 30% of the sintered body and granules after heat treatment when 2-propanol or absolute alcohol is used.

[0040] The step of drying the mixture is carried out to remove the organic solvent, which can be removed by natural drying at 25±5° C. or by drying at 25° C. or higher.

[0041] In the step of forming donor-doped MgO granules from the dried mixture, the MgO granules can be formed from the MgO powder using various methods.

[0042] For example, by rotating a cylindrical container at a rotation speed of 10 to 500 rpm, MgO granules of various sizes can be formed from MgO powder, and MgO granules to which a donor is added can also be formed.Comparing the difference between the powder and the granules, the particle size of the granules is larger than that of the powder.

[0043] The donor-added MgO granules can be prepared by the same method as the above-mentioned method for forming MgO granules, and the donor-added MgO granules can be prepared in a form in which the donor is dispersed on the surface of the MgO granules.

[0044] The step of heat treating the donor-doped MgO granules may be performed at 800 to 1800°C.

[0045] During the heat treatment, some of the donors are transferred to the surface of the granules and form a surface oxide layer containing MgO and the donors, so that a surface oxide layer containing MgO-donors is formed on the surface of the MgO granules during the heat treatment step.

[0046] The heat treatment is preferably performed at a temperature of 800 to 1800° C., and if the temperature is outside this range, an oxide layer may not be sufficiently formed as a surface protective layer on the surface of the MgO granules.

[0047] As in the above-mentioned manufacturing method, when magnesia is manufactured using Mg(OH)2 powder as a starting material, the steps of adding a donor and distilled water to Mg(OH)2 powder to form a mixture, drying the mixture, forming Mg(OH)2 granules to which the donor has been added from the dried mixture, and heat-treating the Mg(OH)2 granules to which the donor has been added can be included to manufacture magnesia. The donor and heat treatment are the same as those described above.

[0048] FIG. 1 is a conceptual diagram of the formation of a surface oxide by heat treatment during the production of MgO granules of the present invention, and a photograph of the surface and internal microstructure.

[0049] As shown in Figure 1, some donors during the heat treatment process move along the grain boundaries and gather on the surface of the granules. As a result, a surface oxide layer with a different composition from the inside of the MgO granules is formed on the surface of the granules.

[0050] In the present invention, the low moisture absorption resistance of MgO can be improved by the formation of a surface oxide layer.

[0051] In this way, in the present invention, MgO powder raw material or Mg(OH)2 powder raw material is used to form MgO granules or Mg(OH)2 granules to which a donor is added, and then heat-treated to produce magnesia. This forms a surface oxide layer containing MgO and a donor like a protective layer on the surface of the MgO granules, ensuring moisture absorption resistance and excellent thermal properties.

[0052] For example, Mg and Mg2TiO4, which contains one or more metal elements in addition to Mg, Zr 0.904 Mg 0.096 O 1.904The surface oxide layer containing metal oxides such as ZnO, ZnO, and ZnO has the effect of improving the moisture absorption resistance of MgO by taking advantage of the free point in the moisture absorption problem.

[0053] The magnesia produced from the MgO powder raw material or Mg(OH)2 powder raw material of the present invention includes MgO granules and a surface oxide layer formed on the surface of the MgO granules, wherein the composition of the surface oxide layer is different from the composition inside the MgO granules, and the surface oxide layer contains MgO and a donor.

[0054] The donor is a metal oxide having a higher metal valence than MgO, and includes one or more of TiO2, Nb2O5, ZrO2, Ga2O3, Mn2O3, B2O3, Fe2O3, SnO2, MnO2, SiO2, V2O5, Ta2O5, Sb2O5, Y2O3, Eu2O3, Er2O3, and Al2O3.

[0055] The donor (metal oxide) material may be contained in an amount of 0.01 to 10.0 wt.%, preferably 0.01 to 2.0 wt.%, relative to 100 wt.% of the total magnesia.

[0056] Specifically, the magnesia (MgO) contains TiO2 and Nb2O5 and satisfies the following formula 6.

[0057] Formula 6 MgO+xwt.%TiO2+ywt.%Nb2O5

[0058] In the above formula 6, x and y are 0 <x、y≦2.0である。

[0059] FIG. 2 is a photograph of the microstructure showing the shape and size of MgO granules produced according to the production method of the present invention, and a photograph of the surface microstructure before and after heat treatment (1400° C., 2 h).

[0060] Referring to Figure 2, MgO granules of various sizes can be produced depending on the production conditions (rpm). Compared to the MgO granules before heat treatment, the surface oxide layer of the MgO granules after heat treatment shows a dense microstructure.

[0061] FIG. 3 is a photograph showing the difference in resistance to water reaction between MgO raw material powder and MgO granules that have been heat-treated (1400°C, 2 hours) after adding a donor to the MgO powder.

[0062] The MgO raw powder was a powder to which no donor was added, and when it was kept in an environment of 85°C and 85% humidity for 72 hours, Mg(OH)2 was observed on the surface of the powder.

[0063] On the other hand, when granules were prepared using donor-added MgO powder according to the manufacturing method of the present invention and heat-treated at 1400°C, no Mg(OH)2 was observed on the surface of the granules when they were maintained in an environment of 85°C and 85% humidity for 72 hours.

[0064] These results indicate that when a donor is added to the MgO powder raw material to form MgO granules and then heat-treated as in the present invention, the granules do not react with water and the moisture absorption resistance is improved.

[0065] Figure 4 shows the microstructure of the fracture surface of a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen (left) and a MgO+0.3wt.%TiO2+0.3wt.%Nb2O5 specimen (right) that were heat-treated at 1400℃ for 2 hours, showing the thickness of the surface oxide layer.

[0066] After heat treatment, the donor-added MgO formed a surface oxide layer that was distinct from the inside of the specimen (granule). In the MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen, it was confirmed that a surface oxide layer of 0.1μm to 3μm thick containing MgO-donor was formed. In the TEM image of the MgO+0.3wt.%TiO2+0.3wt.%Nb2O5 specimen, a surface oxide layer thinner than 0.1μm was also observed.

[0067] Figure 5 shows the energy dependence of the formation of a surface oxide layer containing MgO-donors on the MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+0.2wt.%SiO2 specimen heat-treated at 1400℃ for 2 hours. These are the results of Dispersive X-Ray Spectroscopy (EDS) analysis and photographs of the microstructure.

[0068] When the donor-doped MgO was heat-treated, a surface oxide layer of a different phase from the interior was formed.

[0069] It was confirmed that the MgO content was higher inside the sintered specimen than on the surface, which means that a surface oxide layer containing MgO-donors was formed on the surface of the sintered body.

[0070] The donor content in the surface oxide layer was higher than that in the MgO granules. This indicates that the donor was added at 2.0 wt.% or less for 100 wt.% magnesia, and the donor concentration in the surface oxide layer was higher than the average donor concentration in the whole (granules and surface oxide), and therefore the donor content in the surface oxide layer was higher than that in the granules. The difference was measured to be at least 2 times, preferably 3 times, and more preferably 10 times higher than the donor content in the granules.

[0071] The high thermal conductivity magnesia (MgO) composition according to the present invention contains TiO2, Nb2O5, ZrO2, or Al2O3 in a MgO base and satisfies the following Formula 1, Formula 2, Formula 3, or Formula 4.

[0072] Formula 1: MgO + x wt.% TiO2 Formula 2: MgO + y wt.% Nb2O5 Formula 3: MgO + z wt.% ZrO2 Formula 4: MgO + w wt.% Al2O3 (In Formulas 1 to 4 above, x, y, z, and w satisfy 0 < x, y, z, w ≤ 10.0.)

[0073] Preferably, x in Formula 1 satisfies 0 < x ≤ 10.0, y in Formula 2 satisfies 0 < y ≤ 5.0, z in Formula 3 satisfies 0 < z ≤ 4.0, and w in Formula 4 may satisfy 0 < w ≤ 0.8. More preferably, y in Formula 2 may satisfy the range of 0 < y ≤ 1.0.

[0074] Referring to FIG. 6 and Table 1, it can be seen that when TiO2 is added as a donor to the magnesia (MgO) in an amount exceeding 0 wt.% and not exceeding 10.0 wt.%, the thermal diffusivity of the magnesia (MgO) ceramics according to the present invention increases.

[0075] In particular, referring to FIGS. 6, 8, and Table 1, when TiO2 is added as a donor to the magnesia (MgO) in an amount exceeding 0 wt.% and not exceeding 2.0 wt.% and sintered at 1400 °C, it can be seen that the thermal diffusivity is similar to or more excellent than that of magnesia (MgO) ceramics sintered at 1700 °C.

[0076] In addition, referring to FIG. 6, FIG. 8 and Table 1, when titanium dioxide (TiO2) is added to magnesia (MgO) as a donor in an amount of more than 0 wt.% to 10.0 wt.% and sintered at 1300°C to 1400°C, it shows a high relative density of 96% or more in all compositions, which is significantly improved compared to the relative density of 80-90% of magnesia (MgO) ceramics sintered at the same sintering temperature.

[0077] In addition, it can be confirmed that the thermal diffusivity of the composition in which titanium dioxide (TiO2) of more than 0 wt.% and not more than 10.0 wt.% is added to the magnesia (MgO) sintered at a low temperature of 1300°C to 1400°C is higher than the thermal diffusivity of magnesia (MgO) sintered at the same sintering temperature.

[0078] 7 and 8, when niobium pentoxide (Nb2O5) is added to magnesia (MgO) as a donor in an amount of more than 0 wt.% to 5.0 wt.% or less, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention sintered at 1300°C to 1400°C is similar to or better than that of the magnesia (MgO) ceramic sintered at 1700°C.

[0079] In particular, referring to Figures 7 and 8, when niobium pentoxide (Nb2O5) is added to magnesia (MgO) as a donor in an amount of 1.0 wt.% or less, the thermal diffusivity of the specimen sintered at 1400°C is superior to that of the magnesia (MgO) ceramic sintered at 1700°C.

[0080] In FIG. 9, it can be seen that by fixing TiO2 at 0.3 wt.% and further adding Nb2O5, an improvement in the thermal conductivity properties is observed up to 1.0 wt.%.

[0081] Referring to FIG. 10, when zirconium oxide (ZrO2) is added to the magnesia (MgO) as a donor in an amount of more than 0 wt.% to 4.0 wt.% or less, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention sintered at 1400°C is similar to that of the magnesia (MgO) ceramic sintered at 1700°C.

[0082] Referring to FIG. 11, even when titanium dioxide (TiO2), niobium pentoxide (Nb2O5) and zirconium oxide (ZrO2) are added to the magnesia (MgO) as donors, the thermal diffusivity of the specimen sintered at 1300°C to 1400°C is similar to or better than the thermal diffusivity of the magnesia (MgO) ceramic sintered at 1700°C.

[0083] In particular, referring to FIG. 11, when 0.3 wt.% of titanium dioxide (TiO2), 0.3 wt.% of niobium pentoxide (Nb2O5) and 0.05 wt.% or less of zirconium oxide (ZrO2) are added to the magnesia (MgO) as donors, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention is significantly higher than that of the magnesia (MgO) ceramic sintered at 1700°C.

[0084] Referring to FIG. 12, when more than 0 wt.% to 0.8 wt.% of alumina (Al2O3) is added to magnesia (MgO) as a donor, the thermal diffusivity of the magnesia (MgO) ceramic according to the present invention is increased.

[0085] In FIG. 13, even when the TiO2 and Nb2O5 contents were fixed at 0.3 wt.% and Al2O3 was further added, the thermal conductivity did not decrease significantly, and a similar tendency in the thermal conductivity characteristics was observed.

[0086] The high thermal conductivity magnesia (MgO) composition according to the present invention contains TiO2, Nb2O5 and ZrO2 in an MgO matrix and satisfies the following mathematical formula 5.

[0087] Formula 5 MgO+0.3wt.%TiO2+0.3wt.%Nb2O5+zwt.%ZrO2

[0088] In the above formula 5, z is 0 <z≦0.05である。

[0089] As described above, referring to FIGS. 6 to 13 and Table 1, it can be seen that the specimens in which a small amount of one or more metal oxide compositions selected from TiO2, Nb2O5, ZrO2, Ga2O3, Mn2O3, B2O3, Fe2O3, SnO2, MnO2, SiO2, V2O5, Ta2O5, Sb2O5, Y2O3, Eu2O3, Er2O3 and Al2O3, which have a valence of 3 or more and can act as a donor, are added to MgO, have improved thermal properties compared to the specimens in which no donor is added to MgO.

[0090] The method for producing magnesia ceramics of the present invention includes the steps of adding and mixing a donor to magnesia (MgO) to produce any of the high thermal conductivity magnesia (MgO) compositions, drying the composition, and sintering the composition. The sintering can be performed at 1200°C to 1500°C.

[0091] In low-temperature sintering of magnesia (MgO), low-temperature sintering can be achieved by adding one or more substances that can act as donors, which improves the sinterability.

[0092] The donor includes one or more of TiO2, Nb2O5, ZrO2, Ga2O3, Mn2O3, Fe2O3, SnO2, MnO2, SiO2, V2O5, Ta2O4, Sb2O5, Y2O3, Eu2O3, Er2O3, and Al2O3.

[0093] The magnesia (MgO) ceramics of the present invention is manufactured by adding an appropriate amount of titanium dioxide (TiO2), niobium pentoxide (Nb2O5), zirconium oxide (ZrO2) and / or alumina (Al2O3) as donors to magnesia (MgO), mixing them in a ball mill using 2-propanol as a solvent, then crushing and drying the mixture. The dried mixed powder is molded in a circular metal mold with a diameter of 15 mm at a pressure of 100 MPa, and then sintered in an electric furnace or gas furnace at a temperature of 1200°C to 1500°C for 2 hours.

[0094] The high thermal conductivity magnesia (MgO) ceramics produced by the production method of the present invention has a theoretical density of magnesia (MgO) (3.58 g / cm 3 ) can exhibit relative density values ​​of 93% to 100%. Or, when a donor element heavier than Mg is added, 3.58 g / cm 3 High thermal conductivity magnesia (MgO) ceramics can exhibit densities greater than 10.4 mm. 2 / s~21.9mm 2 It can exhibit a thermal diffusivity value of 100 / s.

[0095] FIG. 14 shows microstructure photographs of the fracture surfaces of a specimen in which 2.0 wt.% TiO2 composition has been added to magnesia (MgO) and a specimen in which 2.0 wt.% ZrO2 composition has been added to magnesia (MgO), after sintering at 1400°C for 2 hours.

[0096] Referring to FIG. 14, when sintered at 1400° C., it shows a very dense microstructure.

[0097] Thus, specific examples of magnesia, its manufacturing method, highly thermally conductive magnesia composition, and magnesia ceramics using the same are as follows.

[0098] 1. Density The measurement was performed by the Archimedes method using xylene.

[0099] 2. Thermal diffusivity The measurements were taken using the laser flash method. (LFA 457,MicroFlash,Netzsch Instruments Inc.,Germany)

[0100] Table 1 shows the density and thermal diffusivity properties of sintered specimens of magnesia (MgO) compositions in the temperature range provided by the present invention.

[0101] [Table 1]

[0102] Example 1: 0.5 wt.% titanium dioxide (TiO2) was added as a donor to magnesia (MgO), and mixed in a ball mill using 2-propanol as a solvent, after which the mixture was crushed and dried.

[0103] The dried mixed powder is molded in a circular metal mold with a diameter of 15 mm at a pressure of 100 MPa, and then sintered in an electric furnace at a temperature of 1300° C. for 2 hours.

[0104] Examples 2 to 32: Highly thermally conductive magnesia ceramics were manufactured in the same manner as in Example 1, except that titanium dioxide (TiO2), niobium pentoxide (Nb2O5), zirconium oxide (ZrO2), alumina (Al2O3), V2O5, B2O3, Y2O3, SiO2, Eu2O3, Er2O3, Fe2O3, etc. were added as donors to the magnesia (MgO) of Example 1 in the amounts shown in Table 1, and these were sintered at a temperature of 1300°C or 1400°C.

[0105] Comparative Example 1: Magnesia ceramics were manufactured in the same manner as in Example 1, except that the donor was not added to the magnesia (MgO) in Example 1.

[0106] Comparative Example 2: Magnesia ceramics were manufactured in the same manner as in Example 1, except that no donor was added to the magnesia (MgO) in Example 1 and the magnesia (MgO) was sintered at a temperature of 1400°C.

[0107] Comparative Example 3: Magnesia ceramics were manufactured in the same manner as in Example 1, except that no donor was added to the magnesia (MgO) in Example 1 and the magnesia (MgO) was sintered at a temperature of 1700°C.

[0108] Referring to Table 1 above, it can be seen that the magnesia (MgO) composition is sufficiently sintered in the temperature range of 1300°C to 1400°C, and that the density and thermal diffusivity of the magnesia (MgO) ceramics change depending on the donor composition ratio.

[0109] Specifically, referring to Examples 1 to 32, when one or more of titanium dioxide (TiO2), niobium pentoxide (Nb2O5), zirconium oxide (ZrO2), alumina (Al2O3), V2O5, B2O3, Y2O3, SiO2, Eu2O3, Er2O3, and Fe2O3 are added to magnesia (MgO) in the sintering temperature range of 1300°C to 1400°C, the magnesia (MgO) ceramic according to the present invention has a density of 3.02 g / cm. 3 ~3.59g / cm 3 It was found that the sintered material showed an excellent density value of 10.4 mm. 2 / s~21.9mm 2 It can be seen that the material exhibits an excellent thermal diffusivity value of 0.1% by mass / s.

[0110] As described above, the high thermal conductive magnesia (MgO) ceramics manufactured by the manufacturing method of the present invention exhibits a high sintering density value compared to conventional magnesia (MgO) ceramics. Therefore, the high thermal conductive magnesia (MgO) ceramics manufactured by the manufacturing method of the present invention exhibits a high thermal diffusivity value compared to conventional magnesia (MgO) ceramics, and can be applied to heat dissipation ceramic materials.

[0111] As described above, the present invention has been described with reference to the drawings illustrating the present invention, but the present invention is not limited to the embodiments and drawings disclosed in this specification, and it is obvious that various modifications can be made by those of ordinary skill in the art within the scope of the technical concept of the present invention. Furthermore, even if the effects of the configuration of the present invention have not been explicitly described in the above description of the embodiments of the present invention, it goes without saying that the effects that can be predicted by the configuration should also be recognized.

Claims

1. (a) adding and mixing a donor to magnesia (MgO) to prepare a magnesia composition; (b) drying the magnesia composition; (c) a step of sintering the dried magnesia composition; wherein in step (a), the donor is added in an amount of more than 0 wt% and not more than 2.0 wt% relative to a total amount of 100 wt% of MgO powder and donor, and said step (c) includes a sintering process at 1200°C or more and less than 1500°C. The donor herein means a metal oxide having a higher metal valence than MgO, that is, an oxide of a metal having a valence of three or more.

2. A magnesia ceramic prepared by the method of claim 1, The present invention includes a sintered body of a magnesia composition including magnesia (MgO) and a donor, The theoretical density of the magnesia (MgO) (3.58 g / cm 3 ) Magnesia ceramics having a relative density value of 93% to 99.9%.

3. A magnesia ceramic prepared by the method of claim 1, A sintered body of a magnesia composition is included, 10.4mm 2 / s~21.9mm 2 Magnesia ceramics having a thermal diffusivity value of .beta. / s.

Citation Information

Patent Citations

  • Ceramic composition

    JP1987132762A

  • High-density magnesium oxide-based sintered compact and its production, and member for plasma treatment apparatus

    JP2000313655A

  • Protective film material for plasma display panel

    JP2005263591A

  • Magnesium oxide vapor-deposition material

    JP2005330574A

  • Magnesium oxide sintered compact

    JP2009067603A